Moving Stroke Rehabilitation Research Evidence into Clinical Practice: Consensus-Based Core Recommendations From the Stroke Recovery and Rehabilitation Roundtable. (November 2019) - Eng, Janice J.; Bird, Marie-Louise; Godecke, Erin; Hoffmann, Tammy C.; Laurin, Carole; Olaoye, Olumide A.; Solomon, John; Teasell, Robert; Watkins, Caroline L.; Walker, Marion F.
Moving research evidence to practice can take years, if not decades, which denies stroke patients and families from receiving the best care. We present the results of an international consensus process prioritizing what research evidence to implement into stroke rehabilitation practice to have maximal impact. An international 10-member Knowledge Translation Working Group collaborated over a six-month period via videoconferences and a two-day face-to-face meeting. The process was informed from surveys received from 112 consumers/family members and 502 health care providers in over 28 countries, as well as from an international advisory of 20 representatives from 13 countries. From this consensus process, five of the nine identified priorities relate to service delivery (interdisciplinary care, screening and assessment, clinical practice guidelines, intensity, family support) and are generally feasible to implement or improve upon today. Readily available website resources are identified to help health care providers harness the necessary means to implement existing knowledge and solutions to improve service delivery. The remaining four priorities relate to system issues (access to services, transitions in care) and resources (equipment/technology, staffing) and are acknowledged to be more difficult to implement. We recommend that health care providers, managers, and organizations determine whether the priorities we identified are gaps in their local practice, and if so, consider implementation solutions to address them to improve the quality of lives of people living with stroke.